O Concílio Vaticano II como objeto de leitura: a formação das culturas conciliares - Caldeira, Rodrigo Coppe (Horizonte, 2019)
The debates over the reception of the Second Vatican Council have grown in the last two decades. In the context of historiography, the reflection on the place of this council in the history of contemporary Catholicism and the discussion about the sources and ways of capturing its reception take its first steps. We move from the concern of constructing a history of the council proper, to the later moment, that is, its reception. In addition to a hermeneutical concern linked to theological concerns, historians of the conciliar reception open new theoretical paths of analysis, but also methodological ones, seeking new ways of approaching the phenomenon. In this way, they are faced with new sources that can collaborate in their understanding. This paper has as main objective to discuss the theoretical possibility that the council takes as an object of reading on the part of certain actors, thus developing what we call conciliar culture: representations about the event constructed by certain groups and that bring their own characteristics. We develop the concept from an approach to Cultural History, particularly that developed by Roger Chartier and offer at the end of the text a brief example of how this perspective can be used, that is, in the study of theological magazines.